Microbiological Substitution of Drug Composition for the Treatment of Generalized Periodontitis in Patients with Diabetes Mellitus - Lenihevych А. М.; Borysenko А. В. (Actual Dentistry, 2025)
Summary. Treatment of periodontal diseases in patients with diabetes mellitus is associated with specific difficulties. This is due to the problems with tissue regeneration and wound healing that these patients have. The use of newer drugs allows for the stimulation of these processes. A drug composition has been proposed for the treatment of generalized periodontitis in patients with diabetes mellitus. To substantiate its clinical use, microbiological studies were conducted to compare the antibacterial activity of several antibacterial drugs. Aim: to determine the antibacterial activity of the proposed drug composition on various strains of microorganisms and mixed microflora of periodontal pockets of patients with diabetes mellitus. Material and methods. For the microbiological study of medicinal products, a technique was used to measure the ability of medicines in a liquid state to penetrate the thickness of agar. This is the so-called agar diffusion method. Results. Determination of antibacterial activity on test strains Staphylococcus aureus (ATCC 27923), Escherichia coli (ATCC 001048), and Candida albicans (ATCC 885663) showed sufficient antibacterial activity of the proposed drug composition. The obtained results of the antibacterial action of the studied drugs on the mixed microflora of periodontal pockets in patients with generalized periodontitis, on the background of diabetes mellitus, show that, according to the assessment of their antibacterial action, etonia, miramistin, and chlorgexidine have a moderate antibacterial effect. Metronidazole and the proposed drug composition have a pronounced antibacterial effect. Conclusions. The obtained results of the antibacterial action of the studied drugs on the mixed microflora of periodontal pockets in patients with generalized periodontitis, on the background of diabetes mellitus, show that, according to the assessment of their antibacterial action, etonia, miramistin, and chlorgexidine have a moderate antibacterial effect. Metronidazole and the proposed drug composition have a pronounced antibacterial effect.